The role of imaging in early diagnosis and prevention of joint damage in inflammatory arthritis. (3rd June 2018) - Yue, Jiang; Wu, Dongze; Tam, Lai-Shan
ABSTRACT: Introduction : Inflammatory arthritis is characterized by chronic inflammation in the synovium, associated with degradation of cartilage and erosion of juxta-articular bone. The bone loss and joint destruction mediated by aberrant immunological responses resulting in proinﬂammatory cytokine release and various immune cell activation are known as osteoimmunology. Areas covered : A structured literature search including Medline and PubMed, Cochrane meta-analyses and abstracts of international congresses was performed to review joint damage in inflammatory arthritis in terms of pathogenesis, novel imaging assessment, and prevention. Expert commentary : Deeper understanding of the integration of the skeletal and immune as well as inflammatory system is paving the way to prevent bone loss and bone destruction in inflammatory arthritis. With the availability of various imaging modalities such as ultrasound, magnetic resonance imaging (MRI) and high-resolution peripheral quantitative computed tomography (HR-pQCT), we are now able to detect early joint damage, early diagnosis of inflammatory arthritis, monitor the progression or even ascertain whether the inflammatory process is effectively suppressed to allow repair of joint damage by novel therapeutic agents.